ASSOCIATIONS OF PSYCHOLOGICAL HEALTH, COGNITION, AND PHYSICAL FUNCTION WITH HEALTH-RELATED QUALITY OF LIFE AMONG STROKE SURVIVORS - Odunlade, Adekola J; Egwu, Michael O; Awotidebe, Taofeek O; Ademoyegun, Adekola; Omisore, Oluwatobi B; Adesokan, Oluwatobi J; Falokun, Ibukun G; Kolade, Adepeju A; Adedoyin, Rufus A (Annals of Allied Health Sciences, 2024)
Objective: To assess the association between Health Related Quality of Life (HRQoL) and psychological health, cognittion, and physical function among Nigerian community-dwelling stroke survivors. Material & Methods: Data on depression, anxiety, cognition, disability, and HRQoL of 102 stroke survivors were assessed with validated instruments. Some important covariates, including post-stroke pain, stroke duration, and sociodemographic variables were assessed as well. Logistic regression analysis was applied. Results: About 47.0% had moderate HRQoL, while the prevalence of depression and anxiety was 36.3% and 26.5% respectively. Low cognition was significantly associated with poor HRQoL (aOR =29.83; 95%CI =25.1–33.0, p<0.001)). Furthermore, patients with normal and borderline anxiety were more likely to have better HRQoL (aOR =0.10 (95%CI=0.05 – 0.19, p<0.001)) and (aOR =0.240 (95%CI=0.08 – 1.21, p=0.018)), respectively. Similarly, stroke survivors with normal depression level (aOR =0.16 (95%CI=0.07-0.63, p<0.001)) and low disability level (aOR =0.13(95%CI=0.05-0.42, p<0.001)) were less likely to have poor HRQoL. Conclusion: Depression, anxiety, cognitive impairment, and disability are independently associated with HRQoL among Nigerian community-dwelling stroke survivors.